Pengaruh Kualitas Pelayanan terhadap Minat Beli Ulang pada Transportasi Online Maxim - Galih Valentino Aji; Handito Lava Daenova (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to determine the influence of service quality on repurchase intention of Maxim online transportation among students at Universitas Pembangunan Jaya. The study employs a quantitative method utilizing SPSS 25 software for hypothesis testing. Measurement instruments in the form of interval scales are used in this research, requiring respondents to express the influence of service quality on repurchase intention when using Maxim through Likert scales. Data collection employs judgmental sampling with a sample size of 150. The results of this research indicate that service quality has a positive influence on the repurchase intention of Maxim online transportation among students at Universitas Pembangunan Jaya..